Screening for Cognitive Impairment among Community-Dwelling Older Adults: A Comparison of 2 Screening Instruments. (July 2021) - Hobden, Breanne; Bryant, Jamie; Freund, Megan; Clapham, Matthew; Sanson-Fisher, Rob
Introduction: Community aged care services provide support to older adults living in their own homes. Cognitive impairment may increase the complexity of the support required. There is a need to ensure suitable brief screening tools are available to community aged care providers to assess possible cognitive impairment. This study aimed to examine the agreement between 2 validated cognitive impairment screening tools, the Mini-Cog, and Abbreviated Mental Test Score (AMTS), and the perceptions the individuals case manager of Case Manager's. Methods: A cross-sectional survey study was undertaken with clients of a community aged care provider. Clients were administered both the screening tools via an electronic survey by their Case Manager. Results: In total, 158 (54%) eligible participants consented to participate. There was a 70% agreement between the Mini-Cog and AMTS measures, indicating a moderate agreement which was not statistically different from chance (Kappa 0.08, 95% CI −0.04-0.19). Case Managers identified 37% (n = 48/130) of participants as possibly having cognitive impairment, of which, 15% (n = 20) were also identified via a screening tool. Conclusions: The findings indicate poor agreement across the 3 measures. To ensure adequate supports are offered to those with cognitive impairment, the use of validated tools that can be administered by non-medical staff in a community setting is a priority. This study highlights a need for further work to determine the most suitable tool for use by community-based aged care services.